Validating the adaptation of the first career measure in isiXhosa: the South African Career Interest Inventory–isiXhosa version. (March 2019) - Rabie, Stephan; Naidoo, Anthony V
South African career counselling practices have predominantly been informed by vocational theories and models developed in the United States and Europe. In view of South Africa's peculiar history and its unique cultural and linguistic environment, the indiscriminate application of Western career models has become increasingly contentious, as the majority of these models fail to account for culture-specific values that influence an individual's career interests, decision-making, and development. The South African Career Interest Inventory was developed to address this contention, through operationalising John Holland's vocational personality theory in South Africa. This study adapted and translated the South African Career Interest Inventory into isiXhosa, in the process constructing the first career interest inventory in a South African indigenous language. Subsequently, we investigated the structural validity of the South African Career Interest Inventory, and therefore Holland's model, on a sample of isiXhosa-speaking secondary school learners ( n  = 266). The randomisation test of hypothesised order relations, multidimensional scaling, and covariance structure modelling were employed to examine the structural validity of the inventory. The results demonstrated the South African Career Interest Inventory–isiXhosa version to be a reliable and valid measure of vocational interest on an early isiXhosa adolescent sample, suggesting the tenability of Holland's model in the South African context. Implications for research and practice are discussed.